MELACAK KONSTRUK METODOLOGI KALENDER ISLAM INTERNASIONAL MOHAMMAD ILYAS - Sakirman Sakirman (Nizham Jurnal Studi Keislaman, 2015)
International Islamic calendar becomes urgent needs of the people. Various attempts have been made so that the Islamic calendar could apply uniformly on an international scale. The need for this is understandable because it can be a symbol of unity of the people and to bridge the differences in execution time of worship, as well as relatively already successfully applied to the determination of prayer times. Until now the International Islamic Calendar pooling efforts have not come to fruition. The problem is that the Islamic organizations tend to keep using the method and criteria for each and have not agreed to the criteria that serve as a common reference. The problem of determining the initial months of the Islamic Calendar generated a lot of difference in their establishment. The difference in the initial determination of an impact on the outbreak of a sense of community and disrupt fervently Muslims in worship, as different in determining when Ramadan, Shawwal, and Dhul-Hijjah which affects the other months. Worse, these differences also impact on other areas such as the political, economic and sociological. Departing from the above problems, Mohammad Ilyas a Muslim astronomer from Malaysia has been donating his scientific career to study the problem of the International Islamic Calendar. In scientific ijtihad, Mohammad Ilyas introduced the concept of the Lunar Date Line Between Nations (International Lunar Date Line). The line is connected between the regions to obtain uniformity hilal Mohammad Ilyas divides the earth into three zones calendar. Methodological construct of the Islamic calendar offered Mohammad Ilyas can be said can not solve the problem, this needs to be a review of the system associated with the prevailing international calendar by using various multi-disciplinary approach and to not ignore universal continuous dialogue. Keywords: International Islamic calendar, International Date Line, Mohammad Ilyas Pendahuluan Mohammad Ilyas adalah pemerhati dan penggagas Kalender Islam Internasional, dilahirkan di India dan kini menetap di Malaysia sebagai guru besar tamu Universitas Malaysia Perlis. Sebelumnya ia adalah guru besar Sains dan Atmosfer di Universitas Sains Malaysia. Ia juga merupakan salah seorang pendiri dan konsultan ahli berdirinya Pusat Falak Sheikh Tahrir di Pulau Pinang.[1] Mohamad Ilyas banyak memberikan kontribusi dalam bidang pengembangan ilmu falak, khususnya tentang Kalender Islam. Ia menggagas konsep Garis Batas Tanggal Kamariah Antar Bangsa atau sering disebut dengan International Lunar Date Line (ILDL). Menurut Baharuddin Zainal sebagaimana yang dituturkan oleh Susiknan Azhari dalam Ensiklopedi Hisab Rukyat, dari segi astronomi, khususnya yang berkaitan dengan teori visibilitas hilal, Mohammad Ilyas adalah salah satu ilmuwan Muslim yang berada pada tahap yang sama dengan ilmuwan barat seperti McNally (London), Le Roy Dogget (Washington), Bradley E. Schaefer (NASA) dan Biruni.[2] Mohammad Ilyas adalah seorang fisikawan dan ahli atmosfer, ia banyak menulis tentang astronomi Islam. Salah satu karyanya monumental sekaligus menjadi magnum opusnya adalah A Modern Guide to Astronomical Calculation of Islamic Calendar, Times and Qibla [1] Susiknan Azhari, Ensiklopedi Hisab Rukyat, cet. ke-II (Yogyakarta: Pustaka Pelajar, 2008), hal. 147. [2] Ibid.